2022
DOI: 10.1536/ihj.21-434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lncRNA APF in Peripheral Blood of Patients with Acute Myocardial Infarction Caused by Coronary Heart Disease and its Clinical Significance

Abstract: Coronary heart disease (CHD) is the leading cause of death from cardiovascular disease. This study investigated the expression and clinical significance of long noncoding RNA (lncRNA) autophagy promoting factor (APF) in peripheral blood of patients with acute myocardial infarction (AMI) caused by CHD. Patients with angina pectoris (AP) (n = 80) and AMI (n = 96) and other patients (n = 60) with precordial discomfort but no CHD were included. The serum levels of lncRNA APF, MIAT, MALAT1, H19, CHAST, CDR1AS, miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The results revealed that lncRNA-MALAT1 expression was upregulated in AML patients with sepsis. The overall survival rate was significantly lower in the group with high lncRNA-MALAT1 expression levels than in the group with low expression levels [53]. Artesunate, a derivative of artemisinin, could regulate the expression of apoptosis-related proteins such as Bcl-2, Bax, caspase-3, and PTEN via the PI3K/AKT signaling pathway and promote apoptosis in human AML cells.…”
Section: Role Of Malat1 In Other Diseasesmentioning
confidence: 92%
“…The results revealed that lncRNA-MALAT1 expression was upregulated in AML patients with sepsis. The overall survival rate was significantly lower in the group with high lncRNA-MALAT1 expression levels than in the group with low expression levels [53]. Artesunate, a derivative of artemisinin, could regulate the expression of apoptosis-related proteins such as Bcl-2, Bax, caspase-3, and PTEN via the PI3K/AKT signaling pathway and promote apoptosis in human AML cells.…”
Section: Role Of Malat1 In Other Diseasesmentioning
confidence: 92%
“…Similar findings were also reported by Wang et al, where MIAT was found to be more highly expressed in MI patients, although its expression was not positively correlated with cardiac biomarkers [ 200 ]. Additionally, a more recent clinical study conducted on a Chinese population also observed higher MIAT expression in MI patients compared to normal individuals [ 201 ]. These collective findings provide valuable insights into the potential utility of MIAT as a diagnostic biomarker in the context of MI.…”
Section: Myocardial Infarction Associated Transcript ( Miat...mentioning
confidence: 99%